ANALISA KADAR RESIDU INSEKTISIDA GOLONGAN ORGANOFOSFAT PADA KUBIS (Brassica oleracea) SETELAH PENCUCIAN DAN PEMASAKAN DI DESA DOLAT RAKYAT KABUPATEN KARO TAHUN 2012 - Arnold Maruli; Devi Nuraini Santi; Evi Naria (Lingkungan dan Kesehatan Kerja, 2012)
Analysis the Amount of Insecticide Residue Organophosphate Group on Cabbage (Brassica oleracea)After Washing and Boiling in Dolat Rakyat Village Karo Regency 2012.Insecticide was known to be potentially dangerous to consumers. Risk of insecticide use was insecticide residue may be persist on agricultural products, such as cabbage.The purpose of this research was to know farmer’s insecticide application, insecticide residue on cabbage in Dolat Rakyat Village Karo Regency,and the effectivenes of various chemical solution to reduce the residue.This research was a simple descriptive. The method used was applicable in the examination of laboratory on cabbage and interview using a questionnaire to 3farmers who plant cabbages.The Result showed that the type of insecicides used by farmers was organophosphate and diamida group. Dosage used was appropriate with the regulation with 15 times of spray and interval spray before haverst was less 1 week.On haverst,residue on cabbage was chlorpiryphos with 0,698 mg/kg. Washing with running water reduce the residue by 76,36%, soaking with DWC’s water by 22,64%, vinegar solution by 35,53%, salt solution by 65,90%, bicarbonat solution by 40,97%, lemon solution by 46,99%, washing followed by boilling by 76,93%.It can be concluded that residue on cabbage obtained from Dolat Rakyat village was not exceeded it’s allowable MRL.Washing followed by boiling was found comparatively more effective than washing alone in dislodging the residue.It had been suggested tofarmers toapplyinsecticidesin accordancewith the regulation andconsumers torecognize the importance ofwashing processbefore consumption. Keywords : Cabbage, insecticide residue, washing,boiling